Processing Solid Waste from Cabbage Vegetables and Cow Rumen Contents into Liquid Organic Fertilizer (LOF) in Semangat Village, Merdeka District, Karo Regency - Erna Frida; Vinolina, Noverita Sprinse; Bukit, Ferry Rahmat Astianta; Bukit, Bunga Fisikanta (Talenta Publisher, 2024)
The manufacture of Liquid Organic Fertilizer (LOF) has been carried out with simple methods and equipment in the Semangat Village, Merdeka District, Karo Regency. LOF is made by utilizing waste produced by farmers at the time of post-harvest vegetables such as cabbage, cabbage, carrot leaves and other vegetables. These vegetables can be used because 90% is a liquid. The chopped cabbage waste is mixed with cow rumen and fermented for two weeks, the resulting leachate is fermented again by adding coconut water and LOF is produced which is ready to be used by farmers. With this LOF, farmers can be helped in reducing chemical fertilizers which are quite expensive, so that the costs needed by farmers are less and LOF can increase nutrients in the soil.